Ответы и объяснения

2013-02-24T15:36:31+00:00

3) используем свойство нечетности ф-ий ctg,sin и четность ф-ии cos

-ctg(-a)=ctga  sin(-a)=-sina  cos(-a)=cosa ctga=cosa/sina

 

 cosa       sina          cosa(1+cosa)+ ( sina)^2     cosa+(cosa)^2+(sina)^2        cosa+1             1

-------- + ----------- = ---------------------------------= --------------------------------- = -------------------= --------

 sina       1+cosa              sina(1+cosa)                       sina(1+cosa)              sina(1+cosa)      sina

что и требовалось доказать